(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
To validate the efficacy of viper anti-venom activity, a total of 79 phytochemicals from Phyllanthus emblica and 59 phytochemicals from Tamarindus indica were docked against each of the nine selected viper venom proteins such as basic phospholipase A2 VRV-PL-VIIIa, anticoagulant class II phospholipase A2, acidic phospholipase A2 Drk-a1, neutral phospholipase A2 RVV-PFIIc, L-amino acid oxidase, Russell's viper venom serine proteinase, RVV-V, cytotoxin drCT-1, dabocetin alpha subunit and cysteine-rich secretory protein Dr-CRPK using the tool Autodock. The structure of three proteins viz basic phospholipase A2 VRV-PL-VIIIa (PDB id-1OXL), anticoagulant class II phospholipase A2 (PDB id- 1VIP) and Russell's viper venom serine proteinase RVV-V (PDB id- 3S9A) were downloaded from RCSB Protein Data Bank and remaining targets 3D structures except neutral phospholipase A2 RVV-PFIIc were modelled using the tool SWISS-MODEL. The templates for modelling the structures were selected through BLASTp analysis. The structure of the neutral PLA2 was modelled using the tool I-TASSER. The stability of all the modelled structures were confirmed by Ramachandran Plot and the active site were detected using the tool MetaPocket2. The docked results revealed that both plants contain several inhibitory molecules against all the target proteins and certain compounds such as stigmasterol, β-sitosterol and campesterol, were present in both plants and each of these molecule can inhibit all venom proteins. The overall results substantiate the traditional use of these plants as antidote to snake bites. However, in vitro and in vivo experimental demonstration is essential for practical application of forgoing findings.